2023
DOI: 10.1002/adom.202202833
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Sum‐Frequency Generation in Niobium Oxydichloride NbOCl2 Nanosheets

Abstract: An alternative approach that can address the limitations of IR detectors is to upconvert the IR photons into the ultraviolet (UV)/visible (vis) domain, where room temperature-operating photon detectors are far more efficient. [2] The generation of high-frequency light quanta is also of great interest for a variety of applications such as coherent light sources, [3] photo-therapy, [4] time-domain fluorescence spectroscopy, [5] and nanolithography. [6] Frequency upconversion through a nonlinear parametric sum fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Niobium oxide dihalides (NbOX 2 , X = Cl, Br, I) are 2D vdW materials with unique distorted structures, where Nb stays away from the octahedral center and forms two short and two long Nb–X bonds. ,,, Among them, the larger size of I – anions increases the degree of distortion in NbOI 2 , resulting in high polarizability . Distinguished from most 2D vdW materials, whose inversion symmetry breaking is thickness-dependent, NbOI 2 exhibits an intrinsic noncentrosymmetric structure with a space group of C 2, which results in a large second-order NLO response in both monolayer and bulk crystals .…”
Section: Introductionmentioning
confidence: 99%
“…Niobium oxide dihalides (NbOX 2 , X = Cl, Br, I) are 2D vdW materials with unique distorted structures, where Nb stays away from the octahedral center and forms two short and two long Nb–X bonds. ,,, Among them, the larger size of I – anions increases the degree of distortion in NbOI 2 , resulting in high polarizability . Distinguished from most 2D vdW materials, whose inversion symmetry breaking is thickness-dependent, NbOI 2 exhibits an intrinsic noncentrosymmetric structure with a space group of C 2, which results in a large second-order NLO response in both monolayer and bulk crystals .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, NbOCl 2 crystals have the opportunity to obtain few-layers. [24,25] Here, the few-layer NbOCl 2 were obtained through the liquid exfoliation method. Figure S1, Supporting Information, (left) shows a schematic diagram of the typical preparation method for few-layer NbOCl 2 based on liquid exfoliation method.…”
Section: Resultsmentioning
confidence: 99%
“…An upconversion efficiency of up to 0.004% provides the possibility for designing optical cross‐correlators for ultrashort pulses characterization. [ 25 ] In addition, Su et al reported that NbOCl 2 has high carrier mobility (≈10 4 cm 2 V −1 s −1 ) and strong light absorption in the visible range, implying great application potential in optoelectronics. [ 26 ] More importantly, the positive and negative charge centers of NbOCl 2 do not coincide, causing spontaneous polarization and generating a built‐in electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxide dihalides MOX 2 (M = V, Nb, Ta, Mo; X = Cl, Br, I) have recently emerged as new members of 2D van der Waals materials, exhibiting unique physical properties [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Among them, NbOI 2 has garnered special interest for its ferroelectricity and robust second-order optical nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…The structural similarity to NbOI 2 suggests that TaOI 2 may also exhibit substantial nonlinearity, though the SHG should be absent. While second-order phenomena, including SHG, sum-frequency generation (SFG), and spontaneous parametric down-conversion (SPDC) [ 28 , 30 , 31 ] in MOX 2 have been widely studied, observations of the third-order nonlinear process are still lacking.…”
Section: Introductionmentioning
confidence: 99%